2016
DOI: 10.1002/bem.21961
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields promote in vitro osteoblastogenesis through a Wnt/β‐catenin signaling‐associated mechanism

Abstract: Substantial evidence indicates that pulsed electromagnetic fields (PEMF) could accelerate fracture healing and enhance bone mass, whereas the unclear mechanism by which PEMF stimulation promotes osteogenesis limits its extensive clinical application. In the present study, effects and potential molecular signaling mechanisms of PEMF on in vitro osteoblasts were systematically investigated. Osteoblast-like MC3T3-E1 cells were exposed to PEMF burst (0.5, 1, 2, or 6 h/day) with 15.38 Hz at various intensities (5 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 49 publications
8
42
2
2
Order By: Relevance
“…There have been many clinical trials and experimental studies reporting that PEMFs modulate bone metabolism through the Wnt/β‐catenin pathway . However, few researchers have investigated the Wnt ligands involved in the process, except for Wnt1 and Wnt3a . In the present study, we did not find increased expression of Wnt3a in the bone samples of rats and in vitro cultured osteoblasts treated by SEMFs, but found the significantly increased expression of Wnt10b.…”
Section: Discussioncontrasting
confidence: 65%
“…There have been many clinical trials and experimental studies reporting that PEMFs modulate bone metabolism through the Wnt/β‐catenin pathway . However, few researchers have investigated the Wnt ligands involved in the process, except for Wnt1 and Wnt3a . In the present study, we did not find increased expression of Wnt3a in the bone samples of rats and in vitro cultured osteoblasts treated by SEMFs, but found the significantly increased expression of Wnt10b.…”
Section: Discussioncontrasting
confidence: 65%
“…Means in detail, that MSCs derived from adipocytes differentiate faster and more expressed if they are cultured in a medium favoring osteogenic differentiation. Zhai et al could show that PEMF stimulation with 15.38 Hz at 20 Gs (2 mT) for 2 h/day enhanced osteoblastic functions through amelioration of the cytoskeletal organization; increased proliferation-related gene expressions (including Ccnd 1 and Ccne 1) as well as upregulated gene and protein expressions of collagen type 1of the Runt-related transcription factor 2 and of Wnt/β-catenin signaling (Wnt1, Lrp6, and β-catenin) at proliferation and differentiation phases [78]. In a rat rotator cuff repair model PEMF therapy improves tendon to bone healing.…”
Section: Interactions Of Emf/pemf With "Classical" Cell Biology -In Vmentioning
confidence: 94%
“…Much evidence has suggested that the Wnt/β-catenin signaling pathway acts as a key regulator in PEMF-induced osteogenic differentiation of mesenchymal progenitor cells, bone formation and repair. For instance, in vitro assay studies, gene and protein expressions of canonical Wnt/β-catenin signaling pathway, including Wnt1, LRP6, and β-catenin, were all significantly enhanced after PEMF exposure at both proliferation and differentiation stages of osteoblast-like MC3T3-E1 cells [31]. In addition, except the upregulation of mRNA expressions of Wnt1, Wnt3a, LRP5 and β-catenin in tissue derived mesenchymal stem cells (ADSCs), PEMFs intervention could also reduce the expression of dickkopf1 (DKK1) which usually acts as an inhibitor of Wnt signaling pathway [32].…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%
“…In addition, except the upregulation of mRNA expressions of Wnt1, Wnt3a, LRP5 and β-catenin in tissue derived mesenchymal stem cells (ADSCs), PEMFs intervention could also reduce the expression of dickkopf1 (DKK1) which usually acts as an inhibitor of Wnt signaling pathway [32]. Furthermore, the enhanced Wnt/β-catenin signaling induced by PEMFs notably elevated the expression of proliferation phase related target genes, Ccnd 1 and Ccne 1, and differentiation phase related genes, ALP, OCN, COL1, and Runx2, in osteoblast cells, which accelerated the osteoblasts proliferation, differentiation, and mineralization, three pivotal processes of bone formation [31, 32]. On the other hand, according to in vivo assay studies, PEMFs effectively reversed the bone mass loss and deterioration of bone microarchitecture analyzed by microCT and attenuated biomechanical strength deterioration evaluated by three-point bending test in hind limb-suspended ovariectomized rats through the Wnt/Lrp5/β-catenin signal pathway [33, 34], indicating that activating this pathway by PEMF exposure is beneficial for bone disorders.…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation